الاستثمار والتدهور البيئي وجودة المؤسسات دليل تجريبي من الدول العربية النفطية - الحويج فرج, حسين (جامعة الوادي - University of Eloued, 2023)
This study aimed to examine the relationship among investment, institutional quality and environmental degradation in the Arab oil-producing countries during the period 2002-2019. In order to achieve its objective, the study adopted FGLS method. The main findings of the study indicated a positive relationship between investment and environmental degradation. However, a negative relationship between institutional quality and environmental degradation was captured. Furthermore, the study found that interaction between investment and institutional quality impacts environmental degradation
Investment, environmental degradation and institutional quality Empirical evidence from the Arab oil-producing countries
مقال
Keywords: الاستثمار ; جودة المؤسسات ; التدهور البيئي ; الدول العربية النفطية